Relationships between Religious Struggles and Well-Being among a Multinational Muslim Sample: A Comparative Analysis - AYTEN, ALİ (OXFORD UNIV PRESS INC, 2018)
This investigation applied a cross-sectional comparative methodology to examine the levels, predictors, and consequences of religious struggles among a multinational sample of 706 Muslims recruited in three universities in Israel/Palestine, Turkey, and Malaysia. Participants were asked to provide demographics and complete measures of religious struggles, satisfaction with life, and generalized anxiety. Three main findings emerged from the study: (1) In general, participants reported low levels of religious struggles; (2) Turks scored significantly higher than both Palestinians and Malaysians on religious struggles; (3) higher levels of generalized anxiety were predicted by higher levels of religious struggles among Malaysians only, and lower levels of satisfaction with life were predicted by higher levels of religious struggles among Palestinians and Turks only. These findings suggest that the links between religious struggles and health and well-being among Muslims are complex, and call for a nuanced detailed analysis of the religious struggles phenomenon among this population.
Keywords: generalized anxiety; Muslims; religious struggles; satisfaction with life; SPIRITUAL STRUGGLES; PSYCHOLOGICAL DISTRESS; ISLAMIC RELIGIOUSNESS; UNIVERSITY-STUDENTS; PREDICTORS; STRESS; LINKS; LIFE